2015
DOI: 10.1007/s11356-015-4129-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of a standard protocol for monitoring trace elements in continental waters with moss bags: inter- and intraspecific differences

Abstract: This paper is a contribution for validating a standard method for trace element monitoring based on transplants and analysis of aquatic bryophytes, in the framework of the EC Directive 2000/60. It presents the results of an experiment carried out to assess significant differences in the amount and variability of As, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn in three moss species (Cinclidotus aquaticus, Fontinalis antipyretica, Platyhypnidium riparioides) and two different parts of the moss (whole plant vs apical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Toxic metals concentrations measured in moss bags exposed at site A (Tab. 1 ) were generally in line with values reported for aquatic mosses from unpolluted or lightly polluted rivers [ 28 , 29 ]. This confirmed that site A, at the springs of the Sarno River, is not affected by toxic metal pollution.…”
Section: Discussionsupporting
confidence: 89%
“…Toxic metals concentrations measured in moss bags exposed at site A (Tab. 1 ) were generally in line with values reported for aquatic mosses from unpolluted or lightly polluted rivers [ 28 , 29 ]. This confirmed that site A, at the springs of the Sarno River, is not affected by toxic metal pollution.…”
Section: Discussionsupporting
confidence: 89%
“…In China, use of the moss bag method to determine pollution levels has been documented in Shanghai [ 29 ], Chongqing [ 30 ], and Guizhou [ 31 ]. Moss bags can be used to monitor not only urban air pollution, but also air around volcanoes [ 32 ], tunnels [ 33 ], airports [ 34 ], and bodies of water [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…For biomonitoring studies, there is a strong emphasis on validating study procedures and standardizing sample treatment protocols [33][34][35][36]. The exposure time of samples is also an important consideration [37,38] in active biomonitoring (moving samples from their natural habitat to a monitored/exposure environment to assess contamination).…”
Section: Introductionmentioning
confidence: 99%